Thin Films: 2D Janus Hybrid Materials of Polymer‐Grafted Carbon Nanotube/Graphene Oxide Thin Film as Flexible, Miniature Electric Carpet (Adv. Funct. Mater. 16/2015). (April 2015) - Xiao, Peng; Wan, Changjin; Gu, Jincui; Liu, Zhenzhong; Men, Yonghong; Huang, Youju; Zhang, Jiawei; Zhu, Liqiang; Chen, Tao
Abstract : A 2D ultrathin Janus hybrid of polymer‐grafted CNTs/GO film is fabricated by Y. Huang, J. Zhang, T. Chen, and co‐workers on page 2428 using microcontact printed CNTs/GO as photo active surface to grow polymer brushes by self‐initiated photografting and photopolymerization selectively from one side of CNTs/GO film. The achieved 2D Janus hybrid materials, with polymer layer as insulative carpet and CNTs/GO thin film as conductive element, serve as flexible and miniature electric carpet for heating micro‐/nano devices locally.